2016
DOI: 10.15761/hmo.1000110
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the eccentric loading on the components of the spine

Abstract: The objective of this work is to study the effect of the backpack on the components of the spine system of a child, know the effect of an eccentric load on the intervertebral discs, the creating a 3D model of the spine of child of 80 kg overall weight under the effect of three eccentric load (P2, P3, P4) plus P1 compression load and calculated by the element method ends, For the boundary conditions we fixed the sacrum (Embedding the sacrum). We propose in this section to draw up a comprehensive study of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…This assumption is further supported by studies that looked at stress distribution on the vertebrae and IVDs under different physiological movements using the finite element method (FEM) [46][47][48] . This work showed that the maxima of stress and strain were localized at the dorsal lateral region and in the ventral median region of both IVD and vertebra.…”
Section: Load Transfer In the Spinal Segments Between Th12 And L5mentioning
confidence: 89%
“…This assumption is further supported by studies that looked at stress distribution on the vertebrae and IVDs under different physiological movements using the finite element method (FEM) [46][47][48] . This work showed that the maxima of stress and strain were localized at the dorsal lateral region and in the ventral median region of both IVD and vertebra.…”
Section: Load Transfer In the Spinal Segments Between Th12 And L5mentioning
confidence: 89%
“…Because of the fact that collagen fibres embedded in AF lamellae play the greatest role in the IVD, the structures of the NP and of the AF matrix have also been simplified. Modelling of these structures as linear elements is also proposed by authors of other studies …”
Section: Discussionmentioning
confidence: 99%
“…The bone tissue of the vertebrae and endplates and the interspinous cartilage was described by isotropic, linear‐elastic material properties . The IVD was modelled in accordance with the vertebral model proposed by Schmidt et al, who modelled the structure of the AF as a matrix strengthened with layers of collagen fibres.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations